2010
DOI: 10.1002/adsc.201000188
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Trimethylaluminium‐Promoted One‐Pot Synthesis of Functional Heteroaromatic and Carbocyclic Trifluoroethylamines

Abstract: The synthesis of trifluoroethylamines as amide bond mimics is an interesting topic in current research. They are well known tools in pharmaceutical and agrochemical industry. Other methods described in literature are often restricted to few substrates. We herein report a new synthetic approach towards this class of substances. First, the trimethylaluminium-promoted generation of a trifluoromethyl-ketimine from the corresponding trifluoromethyl ketone and an aniline derivative was investigated. Next, the ketimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…developed a diastereoselective reductive amination of aryl trifluoromethyl ketones 9. During the preparation of this manuscript, the research group of Bräse10 and later that of Zhou11 reported an achiral Lewis acid mediated reductive amination of aromatic trifluoromethyl ketones and an enantioselective palladium‐catalyzed hydrogenation of perfluorinated nonactivated ketimines, respectively. Although the yields as well as the enantioselectivities are good to high, in the latter contribution the drawbacks are the use of relatively high pressures of hydrogen and the expensive and toxic transition‐metal catalyst for the transformation.…”
Section: Methodsmentioning
confidence: 99%
“…developed a diastereoselective reductive amination of aryl trifluoromethyl ketones 9. During the preparation of this manuscript, the research group of Bräse10 and later that of Zhou11 reported an achiral Lewis acid mediated reductive amination of aromatic trifluoromethyl ketones and an enantioselective palladium‐catalyzed hydrogenation of perfluorinated nonactivated ketimines, respectively. Although the yields as well as the enantioselectivities are good to high, in the latter contribution the drawbacks are the use of relatively high pressures of hydrogen and the expensive and toxic transition‐metal catalyst for the transformation.…”
Section: Methodsmentioning
confidence: 99%